Seasonal Dynamics of Marriage and Fertility of Population of Tambov Province in 1915—1916: Experience of Modernization - K. V. Samokhin (Научный диалог, 2021)
The monthly marriage and birth rate of the population of the Tambov province in 1915—1916 is considered in the article. The methodological basis of the work was the theory of modernization, which is considered by the author in the context of the history of Russia in the 19th — first half of the 20th centuries in the classical interpretation of the transition from traditional society to modern. The novelty of the article lies in the introduction into the scientific circulation of data on the seasonal dynamics of marriage and fertility of the Tambovites during the First World War. A comparative analysis of the corresponding numerical indicators among the townspeople and villagers in 1915—1916 with the pre-war period is carried out. The author comes to the conclusion that the seasonal dynamics of marriage and fertility can be used as a quantitative substantiation of such directions of spiritual modernization as the level of secularization and the propensity to innovate. The analysis shows that the general model of the demographic behavior of Tambov residents is generally correlated with the previous periods. The author comes to the conclusion that the revealed differences between the townspeople and villagers of the Tambov province in the studied plan indicate a greater inclination of the former to innovations and their higher level of secularization, and this confirms the position that the Tambov society was only at the initial stage of spiritual modernization.